Characterization of the mouse beta maj globin transcription termination region: a spacing sequence is required between the poly(A) signal sequence and multiple downstream termination elements. - Tantravahi, J (1993)
For the majority of mRNA encoding eukaryotic transcription units, there is little or no knowledge of the elements responsible for transcription termination or how they may interact with RNA polymerase. In this report, we have used recombinant adenovirus reporter vectors to characterize the mouse beta maj globin sequence elements that cause transcription termination. Within the globin 3' termination region, we have identified at least three sequence elements which induce significant levels of transcription termination (> 50%). The smallest functionally active element (64% termination) is 69 bp in length. The natural arrangement of these elements results in a cumulative termination which is greater than 90%. Recognition of the termination elements by RNA polymerase II depends on the presence of a functional poly(A) signal sequence. We demonstrate that efficient transcription termination depends on appropriate spacing between the poly(A) signal sequence and the termination element.